Modern weapons and military equipment for issue 3-2021 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Sweden’s Bigger Badder Gripen Fighter Packs A Lot Of Punch In An Incredibly Efficient Package, The breakthrough: Russia’s T-90M tanks offer all-round upgrades